Gradual Drum Curriculum For Elementary Students: Integrating Reading Notation and Performance Practice - Sembiring, Piter; Sukmayadi , Yudi; Gunara , Sandie (Grenek: Jurnal Seni Musik, 2025)
This research examines the development of the drum curriculum at Favore Music with a gradual approach to reading and playing notation. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results show that a gradual approach to learning drums improves the understanding of notation systematically, starting from simple to complex rhythmic patterns. This learning model integrates hand-foot coordination techniques, improvisation, and exploration of various musical genres. The implementation of this curriculum not only has an impact on improving students' technical skills but also motivates them to learn in a more interactive and enjoyable way. With an adaptive learning structure, this curriculum can be applied in various music education contexts. These findings contribute to innovation in music education, especially in more effective and structured drumming.